PENGARUH HIDRASI DEHIDRASI DAN DOSIS NPK PADA VIABILTAS BENIH KEDELAI - Niar Nurmauli; Yayuk Nurmiaty (JURNAL AGROTROPIKA, 2010)
This research was conducted in March 2009, which included field experiment on the land location between Plant Production Laboratorium and Seed and Breeding Laboratorium, Agriculture Faculty, Lampung University.The treatment was arranged in factorial (3x5) on randomized block design with 3 replications. Homogenity of variation of the data was tested by Bartlett and additive model by Tukey Test. Seperation of mean value tested by F test on 1 and 5 % level.Experiment showed that (1) hidrated dehidrated was better compared to without invigorasi in repering soybean seed viability after being stored for 7 months and mointurized technique was better that imversed. (2) Additional NPK during flowering stage affected seed viability after being stored for 8 months. (3) Moisturized seed on merang paper will increase seed growth persentage by 68,83 % on NPK fertilizer 62,30 kg/ha after 7 month storage.  Key-word: lot, hydration-dehydration, seed, soybean, viability